Occupational risks of development of industrial conditionality in employees of metallurgical enterprise - Sharavara, L. P.; Шаравара, Лариса Павлівна (My University, 2020)
In modern production employees of metallurgical enterprises are exposed to a complex of harmful and dangerous factors of the production environment, which have a detrimental effect on their health and cause the development of occupational diseases. The structure of harmful production factors that affect the body of workers in this industry is a complex that includes increased noise, general and local vibration, ultraviolet radiation and harmful chemicals released into the air of the work area, as well as adverse factors of the labor process, including forced labor. posture and functional overstrain of the extremities